2014
DOI: 10.3109/09513590.2014.895983
|View full text |Cite
|
Sign up to set email alerts
|

Adding the phytoestrogen Cimicifugae Racemosae to clomiphene induction cycles with timed intercourse in polycystic ovary syndrome improves cycle outcomes and pregnancy rates – a randomized trial

Abstract: Adding CR to clomiphene-induction cycles with timed intercourse in polycystic ovarian syndrome improves cycle outcomes and pregnancy rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
64
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(67 citation statements)
references
References 23 publications
2
64
0
1
Order By: Relevance
“…There were 33 RCTs comprising a total of 4349 women with WHO group II anovulation, undergoing 7210 treatment cycles. Of the 33 included studies, participants were women with PCOS (without CC resistance) in 25 studies, women with CC‐resistant PCOS in five studies, women with WHO group II anovulation (with or without PCOS) in two studies and women with WHO group II anovulation (without PCOS) in one study. The characteristics of these 33 included studies are listed in Table .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were 33 RCTs comprising a total of 4349 women with WHO group II anovulation, undergoing 7210 treatment cycles. Of the 33 included studies, participants were women with PCOS (without CC resistance) in 25 studies, women with CC‐resistant PCOS in five studies, women with WHO group II anovulation (with or without PCOS) in two studies and women with WHO group II anovulation (without PCOS) in one study. The characteristics of these 33 included studies are listed in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Pregnancy rate was reported in all RCTs except two; it was reported as clinical pregnancy rate except in four studies in which it was reported as a positive pregnancy test. Ovulation rate per cycle was reported in all RCTs except for four.…”
Section: Resultsmentioning
confidence: 99%
“…Rooibos increased the thickness of the endometrium without inflammation, while the myometrium was unchanged. In this way, this plant increased fertility in mice 29 . Herba menthae haplocalycis) 6 g, which has been studied on 30 women with tubular infertility with GnRHa / FSH / hCG therapy.…”
Section: Resultsmentioning
confidence: 98%
“…In general, phytoestrogens do not appear to have strong phytoestrogenic properties, and even their application does not show adverse and antiestrogenic effects in cases where the endometrial thickness is normal 29 .…”
Section: Erzhi Pilland Siwu Decoctionmentioning
confidence: 99%
“…PE plus CC group had significantly higher clinical pregnancies per cycle (33/192 (17.2%) versus 71/204 (34.8%), p < 0.01), compared to the CC only group. They concluded that adding CR to clomiphene-induction cycles with timed intercourse in polycystic ovarian syndrome improves cycle outcomes and pregnancy rates [10] .…”
Section: Discussionmentioning
confidence: 99%